Evaluación de la presencia de los genes FLO1, FLO5, FLO9 y FLO11 en cepas de Saccharomyces cerevisiae (2013)
ABSTRACT: Since cell-cell attachment enables biomass separation from the fermentation product, flocculant ability of Saccharomyces cerevisiae strains is a relevant characteristic for the ethanol industry, as it reduces operating times and costs. The capacity of S. cerevisiae to adhere to cells and abiotic surfaces is conferred by a specific group of cell wall proteins called adhesions, which are encoded by FLO gene family. The expression of these genes is associated to the response to some stress conditions that are common to both natural environments and industrial fermentations. This study evaluates the presence of genes FLO1, FLO5, FLO9 and FLO11 in S. cerevisiae strains, isolated from natural environments, and in turn, it demonstrates the importance of the identification of FLO genes in native strains for adequate control of flocculation in industrial fermentations.